KESADARAN MEREK DAN MINAT TERHADAP PRODUK SYARIAH PADA PT. BANK. SUMUT SYARIAH CABANG SIBOLGA - Kaharuddin Kaharuddin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study explains brand awareness factors and interest in Islamic products at PT. Bank. North Sumatra Syariah The research methodology used is a descriptive quantitative approach. Data collection was carried out using a questionnaire that had been created based on predetermined research indicators. Implementation of this research by distributing questionnaires to the public who will or have ever made a purchase transaction at PT. Bank. North Sumatra Syariah Sibolga Branch The location of this research is Sibolga. In this study used a sample of 100 responses. The results of this study which shows that the independent variable (X1) Brand Awareness has a t-value of 5.596 and a value of Sig. The value of t_count> t_table is 5,596> 1,984 and Sig. <0.05 which is 0.000 <0.05 and the independent variable (X2) Interest has a t-value of 5.273 and Sig. 0,000. The value of ð‘¡ â„Žð‘–ð‘¡ð‘¢ð‘›ð‘”> ð‘¡ ð‘¡ð‘Žð‘ð‘’ð‘™ is 5.273> 1.984 and the value of ð‘†ð‘–ð‘”. <0.05 which is 0,000 <0.05, from these results it can be concluded that of the two variables can be accepted and shows the effect on Islamic products at PT. Bank. North Sumatra Syariah Sibolga Branch.